Analisis Komparasi Implementasi Steganografi White-Space dan White-Space Modified pada Artikel Terenkripsi AES dalam HTML5 - Rudy Herteno; Dodon Turianto Nugrahadi; Muhammad Sholih Afif; M Reza Faisal; Friska Abadi (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2020)
The level of internet usage continues to increase until now. information exchange requires security that cannot be predicted by others. one technique for securing information is steganography. Steganography techniques are the science and art of hiding information. This technique can hide the content of information in media that cannot be guessed by ordinary people, so as not to arouse suspicion of the people who see it. One of the media that can implement the white-space modified steganography method is HTML pages. in addition, AES (Advanced Encryption Standard) is a lighter encryption security algorithm compared to other algorithms. In this study, plain text that has been encrypted into cipher text is then inserted with white-space and white-space modification steganography techniques. Data changes have occurred but only less than 1 percent. In experiments that have been implemented on Google Chrome and Mozilla Firefox are the same except in Internet Explorer, which changes the data slightly larger.The implementation of AES encryption and stegano white-space original, has 100% success but the 80% decryption process is successful, but the decryption results contain additional binaries. This happen because the use of tabulation (tabs) instead of spaces in HTML5 articles, and this is often found in HTML articles. while the implementation of AES encryption and stegano whitespace modified, has a success of 100% and the decryption process of 90% succeeded without any changes. 1 article failed because the number of articles is too small compared to the amount of space provided. The conclusion that implementation of AES encryption and white-space modified is more appropriate to be implemented in HTML5 articles, and than the use of tabulation and the number of characters also consequences on the implementation.Keywords: Information, Steganography, White-space modified, Security, AES, Web Browser